Effectiveness of Training for 11-13 year-old Soccer Players on the Basis of Small and Supporting Games in the Context of Action Efficiency in the Situation of a One Against One Game - Andrzej Lachowicz (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2017)
A particular meaning in contemporary soccer games is gained by the efficiency of actions in the situation of a 1 on 1 game. The application of an increased number of exercises based on small and supporting games in soccer training can help to increase the effectiveness of training in this aspect. The aim of the work was to determine the effectiveness of training for 11–13 year-old soccer players with the use of small and supporting games to improve actions during a one against one game. The tests were applied to a group of 11–13 year-old soccer players. We have conducted a pedagogical experiment, the fundamental element of which was to apply training based on small and supporting games in the experimental group, and then tracing the changes on the background of the comparative group. In order to diagnose differences in the effects of training, we have applied a set of test tasks (cycle of 1 × 1 simulation games, test of general physical fitness INKF). The applied training improved the actions in 1 × 1 simulation games. Throughout the experiment, the players from both teams presented a comparable level of the tested motor skills. The training based on small and supporting games seems to be an effective method of increasing training effectiveness in the context of action improvement in the situation of a 1 × 1 game.